Sociological Theory Beyond the Canon - Alatas, Syed Farid; Sinha, Vineeta (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book expands the sociological canon by introducing non-Western and female voices, and subjects the existing canon itself to critique. Including chapters on both the 'founding fathers' of sociology and neglected thinkers it highlights the biases of Eurocentrism and androcentrism, while also offering much-needed correctives to them. The authors challenge a dominant account of the development of sociological theory which would have us believe that it was only Western European and later North American white males in the nineteenth and early twentieth century who thought in a creative and systematic manner about the origins and nature of the emerging modernity of their time. This integrated and contextualised account seeks to restructure the ways in which we theorise the emergence of the classical sociological canon. This book's global scope fills a significant lacuna and provides a unique teaching resource to students of classical sociological theory.- Resumé vydavatel
Keywords: sociologie -- dějiny; sociologie; filozofie; sociology -- history; sociology; philosophy; elektronické knihy; monografie; electronic books; monographs